PENGEMBANGAN WIRAUSAHA MUDA DI MAGUWO, BANGUNTAPAN, BANTUL MELALUI PELATIHAN PEMBUATAN SABUN CUCI PIRING - Mega Karina Putri; Aji Tetuko (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
The knowledge of the community, especially yaoung people who are not yet qualified for chemicals and how process the, has closed business opportunitiesin Maguwo, Banguntapan, bantul. One of product that is easy to process, useful and needed for routine household is dish soap. Thi service aims to provide knowledge and sklills in processing chemicals through training activities in making dishwashing soap and morivating young people to be interested in having a career as entrepreneurs. Service activities are carried out with the trainingmethod that begins a pretest, providing a brief explanation regarding the formula and the function of the ingredients in the formula, manufacturing practice, and evaluation. The dish soap formula used is texapon, NaCl, sodium sulfate, antibacterial agent, lemon fragrance, green dye, and water. Thirty liters of dish soap made during the event. Traning evaluation is carried out to determine the success of the activity. The result is an increased in participants’ knowledge of 55%. Training activities as a from of community service helped participants in understanding and applying of the ingredients and knowing the functions of the ingredients in the dish soap formula